Cultural heritage value in cultural industry development in Hanoi - Thuy, Doan Thanh; Vuong, Ngo Minh (Journal of Posthumanism, 2025)
Hanoi - the capital of a thousand years of civilization, is not only the political, economic and cultural center of Vietnam but also a treasure trove of cultural heritage. Hanoi's heritages are witnesses of time, reflecting the ups and downs and heroic stories of the nation. With 5,922 relics, 1 world cultural heritage, 1,793 intangible cultural heritages; of which 3 heritages are recognized by UNESCO as representative intangible cultural heritages of humanity, 1 world documentary heritage (Hanoi Department of Culture and Sports), Hanoi has great advantages to exploit heritage values ​​in developing the cultural industry. The article introduces the potential of cultural heritages, analyzes the value of heritages in promoting the cultural industry in Hanoi. From there, the article proposes solutions to promote the value of heritages to develop the cultural industry in Hanoi today.